(untitled) (Proceedings of the International Conference on Education, 2025)
The aim of this research is to analyze the role of higher education institutions in developing critical thinking skills in the post-truth era, where misinformation and difficulties in identifying objective truth pose significant challenges. Using bibliometric methods, this study explores academic publications related to the role of universities in countering the adverse effects of the post-truth era. The data analyzed includes journal articles, books, and conference proceedings published over the past decade, focusing on publication trends, author collaborations, and institutional contributions in this field. The analysis results indicate that research on the role of universities in the post-truth era began to be examined starting in 2017 and has continued to increase until now. The countries most extensively studying this theme are the United States and United Kingdom, with 56% of their studies originating from social sciences. This topic is highly intriguing and needs further exploration within other scientific fields such as psychology, health, and communication given that global societal challenges with technological advancements demand a more critical approach to receiving and processing information. Academics and scientists at universities are expected to strengthen their roles by providing scientific truths and raising public awareness for more critical information processing. Further studies are needed to explore these findings across various disciplines so that universities can maintain their role as academic centers for scientific truth into the future while translating anticipatory measures into policy actions.